2017
DOI: 10.1111/risa.12858
|View full text |Cite
|
Sign up to set email alerts
|

Who Would Be Willing to Accept Disaster Debris in Their Backyard? Investigating the Determinants of Public Attitudes in Post‐Fukushima Japan

Abstract: In the wake of the 2011 Great East Japan Earthquake and tsunami, the Ministry of Environment in Japan asked municipalities nationwide to accept and treat disaster waste. This call for cross-jurisdictional waste treatment provoked considerable public controversy. To explore how the national and municipal governments can seek more public acceptance in the wake of future disasters, this study implemented a nationwide survey and addressed the question of what factors influence the public's willingness to support t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…By means of oxidative stress ACCEPTED MANUSCRIPT biomarkers, Noh et al (2015) verified that there was a significant relation between long-term cleanup and threats to human health. Similarly, waste generated from the Fukushima nuclear exposure incident was rejected by numerous residents due to consideration of safety, especially families with children four years old or younger (Aoki, 2018). Indeed, an inappropriate disposal of disaster waste may result in resistance of residents.…”
Section: Communitiesmentioning
confidence: 99%
“…By means of oxidative stress ACCEPTED MANUSCRIPT biomarkers, Noh et al (2015) verified that there was a significant relation between long-term cleanup and threats to human health. Similarly, waste generated from the Fukushima nuclear exposure incident was rejected by numerous residents due to consideration of safety, especially families with children four years old or younger (Aoki, 2018). Indeed, an inappropriate disposal of disaster waste may result in resistance of residents.…”
Section: Communitiesmentioning
confidence: 99%
“…Even in a well-organized community in terms of prevention, such as the Japanese community, the results of a case study on the citizen's perception on municipal plans to host disaster waste suggest that the national and municipal governments should communicate more with the public about the risks of the territory and carry out some initiatives to improve public trust in the national government [73].…”
Section: Evaluation Of the Trust Relationship Between Citizens And Exmentioning
confidence: 99%
“…Although the present study investigated the effects of trust and its determinants on support for the Project, previous research has shown that other variables such as perceived risks and benefits are also related to support, and some have integrated these variables into a model along with trust, its determinants, and support (Siegrist, 1999(Siegrist, , 2000Siegrist, Cvetkovich, & Roth, 2000). The present study did not focus on these variables because perceived risks and benefits have been studied in previous research (Aoki, 2018), and trust has gathered great attention in public opinion and academic circles in Japan as compared to more "rational" concepts of risk and benefit. The Project, however, obviously has both benefits (i.e., gaining a better understanding of the influence of information) and risks (i.e., risk of spreading contamination).…”
Section: Limitations and Future Researchmentioning
confidence: 98%
“…Emphasising this aspect of trust, Cvetkovich and Nakayachi (2007, p. 224) defined trust as a psychological state of "willingness to rely" or cooperate because of one's positive expectations of another person's intentions or behaviour. From this point of view, it is not surprising that trust for a particular agency has been regarded as an important antecedent of support for a particular policy or measure conducted by the agency (Siegrist, 2000), and numerous studies have hypothesised and reported a positive relationship between trust and support (Aoki, 2018;Cvetkovich, Siegrist, Murray, & Tragesser, 2002;. Based on this theoretical and empirical background, the first hypothesis posits that support for the Project is determined by trust in the agency responsible for the Project-the MoE.…”
Section: Prior Research On Trustmentioning
confidence: 99%